Entrepreneurial Knowledge, Social Media, and Entrepreneurial Readiness: The Mediating Role of Entrepreneurial Mindset - Sukarja Sukarja; Agus Wibowo; Suparno Suparno (Jurnal Pendidikan Ekonomi, 2024)
This present study aims to evaluate the influence of entrepreneurial knowledge, entrepreneurial mindset, and the use of social media on entrepreneurial readiness among university students. Primary data were obtained from 165 university students in Jakarta of Indonesia through an independent survey with an online questionnaire. Structural Equation Model Partial Least Square (PLS-SEM) techniques with Smart-PLS applications were used to analyze the retrieved data. The results indicate a positive and significant influence of entrepreneurial knowledge and entrepreneurial mindset toward entrepreneurial readiness among university students. This finding also reveals that the role of entrepreneurial mindset in mediating relationship between entrepreneurial knowledge and the social media usage on entrepreneurial readiness. The implication is that increasing understanding and entrepreneurial attitudes is crucial, while utilizing social media effectively as preparation for digital entrepreneurship. The variable of entrepreneurial knowledge plays an important role in providing the necessary understanding of the practical and theoretical steps in starting and managing a venture.   Keywords: entrepreneurial knowledge, mindset, social media, entrepreneurial readiness